Design and synthesis of quasi dual-mode, elliptic coaxial filter - Cheab, S. (Czech Technical University, 2015)
This article introduces the design of a novel quasi dual-mode, elliptic coaxial filter. The transfer function is mapped to a Generalized Chebyshev prototype with symmetrically located transmission zeros (TZs) where the coupling values are extracted. Furthermore, the miniaturization is achieved by incorporating stepped-impedance coaxial line with inductive element shunted at the center to exhibit a quasi dual-mode property. Theoretical analysis together with experimental prototype is presented. The center frequency of the filter is 2.7 GHz. The simulated and measured insertion loss/return loss are 1.2 dB/15 dB and 2.5 dB/11.5 dB respectively. Both theoretical and measured results show a very good agreement.